DEEP STRUCTURE OF THE LITHOSPHERE AND DYNAMICS OF JUNCTURE ZONES OF UKRAINE AND BALTIC SHIELDS - Chekunov A.V.; Mitrovanov F.P.; Tripolskiy A.A.; Sharov N.V.; Kharitonov O.M.; Zagorodnyy V.G. (My University, 1992)
Data on the geophysics and geology of the jointing zones separating the areas of Archean and early Proterozoic consolidation of the Ukrainian and Baltic shields were compared. It was discovered that the deep structure and geology of these zones are very similar, making it possible to regard them as geotectonic equivalents. On this basis a unified geodynamic model is suggested in which the action of the deep-seated early Proterozoic asthenolith is decisive, transforming the continental substrate of the Archaean to form jointing zones with a thickened crust along the edge and gabbroid plutons with rapakivi granites in the centre. The results obtained are significant for the solution of both regional and general questions of tectonogenesis and geodynamics.
Keywords: Archaean; Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Архей; Precambrian::Archean; Докембрий::Протерозой